Probiotic fermentation enhances bioaccessibility of lycopene, polyphenols and antioxidant capacity of guava fruit (Psidium guajava L) - Harshpinder Kaur; Moushumi Ghosh (Journal of Agriculture and Food Research, 2023)
This study investigated bio-accessibility of lycopene and total polyphenols using simulated gastrointestinal digestion, in guava pulp (Psidium guajava L) pulp fermented with two probiotic LAB strains Lactococcus lactis subsp lactis and Lactobacillus casei. Physicochemical parameters, and antioxidant contents were also evaluated. Results indicated that LAB fermentation reduced the pH of pulp from 3.8 to 2.6, with increase of TA and reduced the TSS content of the pulp to 13.06 and 12.67◦Bx, respectively after 8 h of fermentation. Compositional analysis of fermented guava pulps indicated decrease in carbohydrates (29.6%), lipids (4.6%), moisture (19.7%) and slight increase in proteins (0.7%). The total poly phenolics (701mg/GAE/g) and DPPH radical scavenging activity (81%) was significantly (p < 0.05) higher in comparison to unfermented counterparts while Vitamin C content was not affected. Guava pulp fermented by both strains improved overall sensorial acceptability with no notable differences in sensory scores after storage under refrigerated conditions for up to 7 days. Simulated gastrointestinal digestion studies revealed that pulp fermentation substantially improved the bioaccessibility of total phenols by 70% and 63% and lycopene content by 13.33 and 12.24% in L. lactis and L. casei fermented pulp in comparison to control (unfermented pulp). DPPH free radical scavenging activities of the dialyzable fractions of fermented guava pulp were 71.3 and 69.3% respectively. Overall, the results of this study were encouraging and indicate that fermentation of guava pulp with LAB can potentially enhance bioactives and their subsequent bioaccessibility implying beneficial impacts upon consumption.